Industry sponsored youth smoking prevention programme in Malaysia: a case study in duplicity. (24th November 2004) - Assunta, M; Chapman, S
Abstract : Objective: To review tobacco company strategies of using youth smoking prevention programmes to counteract the Malaysian government's tobacco control legislation and efforts in conducting research on youth to market to them. Methods: Systematic keyword and opportunistic website searches of formerly private internal industry documents. Search terms included Malay, cmtm, jaycees, YAS, and direct marketing; 195 relevant documents were identified for this paper. Results: Industry internal documents reveal that youth anti-smoking programmes were launched to offset the government's tobacco control legislation. The programme was seen as a strategy to lobby key politicians and bureaucrats for support in preventing the passage of legislation. However, the industry continued to conduct research on youth, targeted them in marketing, and considered the teenage market vital for its survival. Promotional activities targeting youth were also carried out such as sports, notably football and motor racing, and entertainment events and cash prizes. Small, affordable packs of cigarettes were crucial to reach new smokers. Conclusion: The tobacco industry in Malaysia engaged in duplicitous conduct in regard to youth. By buying into the youth smoking issue it sought to move higher on the moral playing field and strengthen its relationship with government, while at the same time continuing to market to youth. There is no evidence that industry youth smoking prevention programmes were effective in reducing smoking; however, they were effective in diluting the government's tobacco control legislation.